THE RELATIONSHIP BETWEEN MODES OF EXERCISE AND THE MEASURES IN VISCERAL ADIPOSE TISSUE - Ziolo, Zachary (East Carolina University)
Purpose: The increasing prevalence of obesity observed in the United States should be alarming to our nation, as it effects a large percentage of the population of the United States and is the cause of many thousands of deaths per year (NIH 2022). Obesity leads to many chronic disease states such as metabolic diseases, cardiovascular diseases, or fatty liver diseases. The most influential factor of obesity on chronic health conditions is the visceral adipose tissue (VAT). VAT is most influential due to these adipocytes being more metabolically active, and most VAT containing direct access to the hepatic portal which can lead to ectopic adipose storage. Physical activity and exercise have been shown to reduce VAT mass, however, it has been difficult to determine if resistance training (RT) or aerobic training (AT) are more influential in VAT differences. This study aims to better understand the effects of exercise training compared to a sedentary lifestyle and investigate the changes this will have on body composition. Subjects were separated into a "Highly Active" group and a "Sedentary" or control group. Both groups' body composition measurements were taken with DXA. The subject characteristics and adipose measurements were taken and compared through a 3x1 ANOVA. When comparing the measures of our Sedentary sample to both of the Highly Active groups, VO2 Max was significantly different from the Control Group. For Visceral Adipose Tissue Measures, the Resistance Training was significantly lower when compared to both the Control Group and the Aerobic Training group.
Keywords: Visceral Adipose Tissue; Adipose tissues; Isometric exercise; Aerobic exercises; Obesity